2013
DOI: 10.4155/fmc.13.189
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Inducing Antifungal Agents and Their Activity Against Fungal Biofilms

Abstract: Invasive fungal infections are associated with very high mortality rates ranging from 20-90% for opportunistic fungal pathogens such as Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus. Fungal resistance to antimycotic treatment can be genotypic (due to resistant strains) as well as phenotypic (due to more resistant fungal lifestyles, such as biofilms). With regard to the latter, biofilms are considered to be critical in the development of invasive fungal infections. However, there are only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 132 publications
(167 reference statements)
6
139
0
5
Order By: Relevance
“…However, it has been reported that biofilm formation typically induces several stress response pathways that impair the activity of azole drugs, such as the induction of drug efflux pumps (17). Consequently, cells in a biofilm are up to 1,000-fold more azole resistant than their planktonic counterparts (1,18), supporting the need for new treatments.…”
mentioning
confidence: 99%
“…However, it has been reported that biofilm formation typically induces several stress response pathways that impair the activity of azole drugs, such as the induction of drug efflux pumps (17). Consequently, cells in a biofilm are up to 1,000-fold more azole resistant than their planktonic counterparts (1,18), supporting the need for new treatments.…”
mentioning
confidence: 99%
“…C. albicans is the predominant human fungal pathogen and accounts for 35% of invasive fungal infections (Lewis et al, 2013). C. albicans cells can also grow as a surface-attached biofilm, e.g., on catheters and heart valves, thereby causing recurrent systemic infections (Cuéllar-Cruz et al, 2012;Mayer et al, 2013), which are in general resistant to most antimycotics (De Cremer et al, 2015;Delattin et al, 2014a). In the search for novel antibiofilm molecules, we previously identified OSIP108 as a new antibiofilm peptide (Delattin et al, 2014c).…”
Section: Discussionmentioning
confidence: 99%
“…[3,62] Anti-cancer agents (other than CAP) that act by raising tumor oxidative stress include radiotherapy [63]; photodynamic therapy [64]; many chemotherapeutic drugs [65,66]; and hyperthermia [67,68]. Antiinfective drugs, including many antibiotics [69]; antifungals [70]; and anti-parasitics [71] are known to act, at least in part, by raising oxidative stress in infected cells. From the perspective of this article, these drugs may act by triggering or initiating endogenous RONS and achieve their therapeutic effects via oxynitroso shielding, thus matching part of the cell's own stress response mechanism that can lead to either cellular apoptosis or adaptation.…”
Section: Oxy-nitroso Shielding In Existing Therapiesmentioning
confidence: 99%